Soft Robotic Manipulation of Onions and Artichokes in the Food Industry. (10th April 2014) - Morales, R.; Badesa, F. J.; Garcia-Aracil, N.; Sabater, J. M.; Zollo, L.
Abstract : This paper presents the development of a robotic solution for a problem of fast manipulation and handling of onions or artichokes in the food industry. The complete solution consists of a parallel robotic manipulatior, a specially designed end-effector based on a customized vacuum suction cup, and a computer vision software developed for pick and place operations. First, the selection and design process of the proposed robotic solution to fit with the initial requeriments is presented, including the customized vacuum suction cup. Then, the kinematic analysis of the parallel manipulator needed to develop the robot control system is reviewed. Moreover, computer vision application is presented in the paper. Hardware details of the implementation of the building prototype are also shown. Finally, conclusions and future work show the current status of the project.